The Relation between Parental Locus of Control and Willingness to Implement Parent Management Training Strategies. - Drott, Catherine E.; Elkins, Sara R.; Kritikos, Tessa K. (Child Psychiatry & Human Development, 2026)
In child disruptive behavior treatment, successful parent management training (PMT) outcomes are dependent on parents' use of strategies outside of sessions. This study aimed to identify the influence of parental locus of control (PLOC) on a key treatment acceptability variable: parents' willingness to implement PMT strategies. We sought to investigate this relationship for individual strategies within PMT, given the composite nature of the intervention. In this study, 109 parents of children (ages 2–12) with disruptive behavior watched brief videos detailing three proactive PMT strategies (child-directed interaction, effective commands, positive attention) and three reactive PMT strategies (ignoring, time out, and removal of privileges) and rated their willingness to implement each strategy. Internal PLOC predicted greater overall willingness to use PMT strategies, above and beyond the influence of child age, child gender, and disruptive behavior severity. Notably, the relationship between willingness and PLOC differed across individual strategies. PLOC predicted willingness to implement proactive PMT strategies to a greater degree than willingness to implement reactive strategies. External PLOC may be a greater barrier to use of proactive strategies because of these strategies' misalignment with external PLOC-related beliefs. Results have implications for the personalization of PMT based on parent cognitions, as well as for the separate analysis of individual components of PMT in future research.